Azabicyclo[3.2.0]heptan-7-ones (carbapenams) from pyrrole - Gilchrist, Thomas L. (2012)
The azabicyclo[3.2.0]heptan-7-ones 4, 10, 16 and 24 have been prepared from pyrrole. The same general approach has been used for all these derivatives; namely, substitution of pyrrole at the 2- and 5-carbon atoms, catalytic hydrogenation to produce pyrrolidine-2-acetic acid derivatives, and cyclisation using tris(1,3-dihydro-2-oxobenzoxazol-3-yl)phosphine oxide 6. The catalytic hydrogenation of 2,5-disubstituted pyrroles gives only the corresponding cis-2,5-disubstituted pyrrolidines. The hydrogenation proceeds more easily when the nitrogen atom bears a tert-butoxycarbonyl substituent. The N-tert-butoxycarbonylpyrroles 8 and 21 bearing an á-substituent in the acetate side chain were hydrogenated with a high degree of facial stereoselectivity. This allowed the 6-phthalimidoazabicyclo- [3.2.0]heptan-7-one 24 to be isolated as a single diastereoisomer. The X-ray crystal structure of a precursor, the triester, 22a, has been obtained.